ICBR 2020 1st International Belt and Road Conference - Chung, Ellen; Mathew, Vloreen Nity (UiTM Sarawak, 2021)
UiTM Sarawak, together with Beijing Wuzi University and Asia China Education and Culture (ACEC) Association joined forces to organise the first International Belt and Road Conference (ICBR) on 14th and 15th January 2020. ICBR2020 was supported by Ministry ofToursim, Arts and Culture Sarawak (MTAC), Ministry of Education, Science and Technological Research Sarawak (MESTR), Sarawak Convention Bureau (SCB) as well as the Consulate-General ofThe People’s Republic ofChina in Kuching. Prior to that, UiTM Cawangan Sarawak has signed a Memorandum of Understandings (MoU) with five (5) public universities in China in September 2019. During this trip to China, the idea of organizing the ICBR 2020 was mooted by Rector, Professor Dato Dr. Jamil Haji Hamali. Dr Ellen Chung was assigned as the Conference Chair to organise the conference.